SAT0466 PED-BD COHORT 2013: Expert Consensus Classification Gives Higher Sensitivity than the International Study Group Criteria to Define Behcet's Disease in Children. (23rd January 2014) - Kone-Paut, I.; Darce-Bello, M.; Shahram, F.; Ozen, S.; Cimaz, R.; chkirate, B.; Bouayed, K.; Hofer, M.; Gattorno, M.; Anton, J.; Cantarini, L.; Faye, A.; et al.
Abstract : Background: BD is rarely encountered in children where the disease is very difficult to recognize. The outcome of patients with few symptoms is currently unknown Objectives: To define the outcome of paediatric patients with at least two symptoms of BD, and to obtain an appropriate definition of BD in patients <16y Methods: An international expert committee has defined the criteria of inclusion. New patients or patients followed for a maximum of 3 years, who presented at least 2 symptoms of BD (among a list), and gave their informed consent were included, reviewed yearly. Results: 223 patients (SR: 1), from 22 centres of 12 countries, were included since 2008, median age of 13, 3y (2.3-21y). Median age at first symptom was 8y (9m-18y). Family history of BD was present in 50 (22.4%) and consanguinity in 10 (4.5%). Median disease duration at inclusion was 4.7y (0-16, 5y) and from the first symptom to last visit was 5.5y (1m-19.4y). Inclusion criteria plus oral aphtosis (mandatory) were (%): genital aphtosis 51.1, necrotic folliculitis 31.4, uveitis 28.7, familial history 22%, pathergy test positive 18.8, erythema nodosum 14.3, vascular 10 and retinal vasculitis 7.2. Mean number of symptoms: 1 plus family history (41%), 2 (33%), more than 3 (26%). Patient had a median of 1.0 follow-up visit (0-4). 217 patients had a first visit: where symptoms were as follows (%): genital aphtosis 49, skin lesions 49, joints and fever 41, eyes lesions 35, neurological 34.5, gastrointestinal 30.5 and vascular16.5. HLAB51 was present in 48% and A26 in 4%. Male patients had significantly more uveitis. 138 patients had a 1-y visit (mean BD duration: 5.6y). 81 patients had 2-y (6.3y), 44 a 3-y (7.2y) and 18 a 4-y visit (7.4y). Between 1 st -4 th visit: 62% had no new symptom, 23% had one, and 8% had 2 and 7 had more than 3. The expert committee has reviewed 196 files at a median disease duration of 6, 7y (0.9-19y), and classified 118 patients as definite, 21 as probable and 3 as not BD. 54 charts were reviewed but did not reached consensus. 45 files have been reviewed more than once. Although good concordance (Kappa coefficient = 0.72), International criteria and expert classification showed significant differences: 60.2% (118/196) patients were classified as definite BD by experts, whereas only 45.9% of these patients met the international criteria (P<0.0001). Having 2 or more symptoms was significantly associated with classification as definite BD (p=0.0005). Conclusions: The expert committee has classified the majority of patients in the BD group although they did not fulfil the international BD classification criteria (for adults) Disclosure of Interest: None Declared